Hemoglobin is associated with cardiotoxicity in melanoma patients without anemia receiving immune checkpoint inhibitor therapy - Elias Haj-Yehia; Raluca I. Mincu; Phillip Schulte; Sebastian Korste; Samuel Dautzenberg; Lars Michel; Amir A. Mahabadi; Tienush Rassaf; Matthias Totzeck (International Journal of Cardiology: Heart & Vasculature)
Background: Low hemoglobin values are associated with cardiotoxicity in patients with melanoma and other cancer entities receiving immune checkpoint inhibitor (ICI) therapy. However, in cancer patients under chemotherapy, enhanced incidence of cardiotoxicity events are also reported with increasing hemoglobin values. So far, the association between hemoglobin values within the normal limits and the incidence of cardiotoxicity in melanoma patients treated with ICI therapy has not been examined. Methods: We analyzed 114 melanoma patients receiving ICI therapy (61 ± 13 years; 38 % female) from the prospective Essen Cardio-Oncology Registry (EcoR). Patients with cancer-related anemia (hemoglobin < 11 g/dL) were excluded from the analysis. Baseline hemoglobin levels were assessed at patient enrollment before initiation of ICI therapy. Endpoint was the whole spectrum of cancer therapy-related cardiovascular toxicity (CTR-CVT) according to the European guidelines on cardio-oncology with a median follow-up of 464 days. Results: Hemoglobin values and overall CTR-CVT were positively associated with hazard ratio (HR) rising in a J-shaped curve depending on increasing hemoglobin values. Subgroup analysis revealed only a significant association of hemoglobin and cancer therapy-related cardiac dysfunction (CTRCD) (HR: 1.417; 95 % confidence interval (CI): 1.101 – 1.825; p = 0.007). This association also remained significant after adjustment for further confounders. Conclusions: Hemoglobin values within the normal limits are associated with cardiovascular toxicity in terms of CTRCD in this cohort of melanoma patients receiving ICI treatment. Future studies are needed to investigate underlying mechanisms and validate the clinical utility of hemoglobin as a potential additional biomarker for risk stratification in cancer patients.